2004
DOI: 10.1113/jphysiol.2004.065912
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative effect of S4–S5 loops in domains D3 and D4 on fast inactivation of the Na+ channel

Abstract: Cytoplasmic S4-S5 loops have been shown to be involved in fast inactivation of voltagegated ion channels. We studied mutations in these loops and their potential cooperative effects in domains D3 (N1151C, A1152C, I1160C/A) and D4 (F1473C, L1482C/A) of the human skeletal muscle Na + channel α-subunit (hNa v 1.4) using expression in tsA201 cells and the whole cell patch-clamp technique. All cysteine mutations were accessible to intracellularly applied sulfhydryl reagents which considerably destabilized fast inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 48 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…40,41 Confoundingly, accessibility studies with Na v 1.4 showed that both the DIII S4-S5 and DIV S4-S5 linkers remain accessible when channels are inactivated. 40,42 Mutagenesis work also aided in demonstrating that the S6 segments of DI, DII, and DIV modulate fast inactivation. An alanine-mutagenesis study showed that mutations in the center 43 and in intracellular 44 end of DIV S6 segment in Na v 1.2 inhibited inactivation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Confoundingly, accessibility studies with Na v 1.4 showed that both the DIII S4-S5 and DIV S4-S5 linkers remain accessible when channels are inactivated. 40,42 Mutagenesis work also aided in demonstrating that the S6 segments of DI, DII, and DIV modulate fast inactivation. An alanine-mutagenesis study showed that mutations in the center 43 and in intracellular 44 end of DIV S6 segment in Na v 1.2 inhibited inactivation.…”
mentioning
confidence: 99%
“…47 The C-terminus also plays an important role in modulating Na C channel inactivation. 48 Generally, From N-terminal to C-terminal, the intracellular end of DI S6 segment (DWCW window), 45,47 intracellular end of DII S6 segment, 45 DIII S4-S5 linker, 38,39,42 DIII-DIV linker, [25][26][27][28][29][30][31][32][33] DIV S4-S5 linker, [40][41][42] lower half of DIV S6 segment, 44 , 47 and C-terminus. 23,[48][49][50][51]53 each Na C channel homolog has distinct fast inactivation kinetics.…”
mentioning
confidence: 99%
“…1C ) raises the question whether some of the gating perturbations resulted from a direct interaction between DIV-S6 and the selectivity filter. Thermodynamic mutant cycle analysis has previously been performed to identify direct molecular interactions during inactivation 20 23 . We applied this method to the mutant cycles consisting of wild type, K1237E, single cysteine replacements in DIV-S6 and combination of the latter two constructs.…”
Section: Resultsmentioning
confidence: 99%
“…The DIV VSM activates with the slowest kinetics (Bosmans, Martin-Eauclaire, & Swartz, 2008). Its movement frees an intracellular linker called the inactivation gate that connects DIII helix S6 to DIV helix S1 ( Figure 1A) (Capes, Goldschen-Ohm, Arcisio-Miranda, Bezanilla, & Chanda, 2013) The inactivation gate contains a cluster of hydrophobic residues containing the amino acid sequence IFMT (the IFMT motif) that can now bind to a corresponding inactivation particle receptor lying within the S4-S5 linkers of DII, DIII, and DIV (Popa, Alekov, Bail, Lehmann-Horn, & Lerche, 2004). As a result, the inactivation gate occludes the pore and inactivates the channel within a few milliseconds of opening.…”
Section: Movement Of the Di-diiimentioning
confidence: 99%